Storks - Stoller, Nicholas; Sweetland, Doug; Samberg, Andy, 1978-; Crown, Katie; Grammer, Kelsey, 1955-; Danna, Jeff; Danna, Mychael (Burbank, CA : Warner Bros. Entertainment, 2016)
With the help of his human friend Tulip, Junior, a stork, races to make his first-ever baby delivery before his boss discovers he accidentally activated the Baby Making Machine.
Originally released as a motion picture in 2016.
Dolby digital 5.1, anamorphic wide screen 1.78:1.
Features: The master : a LEGO ninjago short, music video for Jason Derulo's hit song "Kiss the sky."
Photography director, Simon Dunsdon ; production designer, Paul Lasaine ; editor, John Venzon ; music, Jeff Danna, Mychael Danna.
Voices: Andy Samberg, Katie Crown, Kelsey Grammer, Jennifer Aniston, Ty Burrell.
MPAA rating: PG.
Keywords: Storks -- Drama; Infants -- Drama; Delivery of goods -- Drama; Action and adventure films; Computer animation films; Fiction films; Video recordings for the hearing impaired; Feature films; Animated films; Comedy films